Pendekatan Kriptografi Hybrid pada Keamanan Dokumen Elektronik dan HypertextTransfer Protocol Secure (HTTPS) (Analisis Potensi Implementasi Pada Sistem Keamanan) - Basri (JURNAL ILMU KOMPUTER, 2015)
Security issue always to be challenge for the development of information technology. As the security aspects of information systems, both of electronic and document data in hypertext data communications, must be able to meet safety standards. The implementation of security systems calssified as two methods, Symmetric and Asymmetric. Implementation of these methods certainly have their advantages and disadvantages of each, so it is necessary to apply a method to merge some types of the methods. This project was analyzed using a hybrid approach of cryptographic methods that are implemented on the security of electronic documents and Hypertext Transfer Protocol Secure (HTTPS). In the implementation of electronic document used of biometric signatures and DSA (Digital Signature Algorithm) and implementation on HTTPS used a combination of asymmetric cryptography and symmetric cryptography. The analysis of this research translated into the implementation of hybrid method on electronic documents and Hypertext Transfer Protocol Secure. From the analysis shows that the hybrid method is able to combine the advantages of symmetric and asymmetric methods, although of course the constraints in implementation complexity of the system will be even greater.